Optimizing hybrid vigor: a comprehensive analysis of genetic distance and heterosis in eggplant landraces - Rajan, Neha; Debnath, Sandip; Perveen, Kahkashan; Khan, Faheema; Pandey, Brijesh; Srivastava, Akanksha; Khanam, Mehrun Nisha; Subramaniyan, Vetriselvan; Kumarasamy, Vinoth; Paul, Pronob J.; Lal, Mohan (Frontiers Media, 2023)
IntroductionThis study explored the molecular characterization of 14 eggplant (brinjal) genotypes to evaluate their genetic diversity and the impact of heterosis. As eggplant is a vital horticultural crop with substantial economic and nutritional value, a comprehensive understanding of its genetic makeup and heterosis effects is essential for effective breeding strategies. Our aim was not only to dissect the genetic diversity among these genotypes but also to determine how genetic distance impacts heterotic patterns, which could ultimately help improve hybrid breeding programs.MethodsGenetic diversity was assessed using 20 SSR markers, and the parental lines were grouped into five clusters based on the Unweighted Pair Group Method of Arithmetic Means (UPGMA). Heterosis was examined through yield and yield-related traits among parents and hybrids.ResultsPolymorphisms were detected in eight out of the twenty SSR markers across the parental lines. Notably, a high genetic distance was observed between some parents. The analysis of yield and yield-related traits demonstrated significant heterosis over mid, superior, and standard parents, particularly in fruit yield per plant. Two crosses (RKML-26 X PPC and RKML1 X PPC) displayed substantial heterosis over mid and better parents, respectively. However, the positive correlation between genetic distance and heterosis was only up to a certain threshold; moderate genetic distance often resulted in higher heterosis compared to very high genetic distance.DiscussionThese findings emphasize the critical role of parental selection in hybrid breeding programs. The results contribute to the understanding of the relationship between genetic distance and heterosis, and it is suggested that future research should delve into the genetic mechanisms that drive heterosis and the effect of genetic distance variance on heterosis. The insights drawn from this study can be harnessed to enhance crop yield and economic value in breeding programs.